How applicable are results of systematic reviews and meta-analyses of health behaviour maintenance? A critical evaluation. Issue 4 (April 2015) - Loef, M.; Walach, H.
Abstract Objective To evaluate the practical applicability of systematic reviews and meta-analyses to the maintenance of physical activity or weight loss by assessing methodological and reporting aspects. Methods To identify relevant studies a literature search was conducted in MEDLINE, EMBASE, Cochrane Library, PsycINFO, PSYNDEX, Google scholar, and reference lists. Each article was evaluated for methodological quality, operationalization of maintenance, and practicability following the RE-AIM framework and the PRISMA statement. Results Twenty-four systematic reviews and meta-analyses were included of which 14 were published in the last four years. There were multiple definitions of maintenance. In addition the instances of redundancy, and neglect of thematic fields are identified. Eighty-seven percent of the reviews showed methodological flaws. The potential practical use of the outcomes was limited. Conclusion The applicability of systematic reviews and meta-analyses regarding health behaviour maintenance is limited with regard to reporting, methodology and thematic coverage. For practitioners, synthesis of quantitative and qualitative evidence with theoretical models is lacking.